RANCANG BANGUN SISTEM INFORMASI PENDATAAN LAPORAN SKRIPSI DENGAN ANALISA METODE SWOT - Jamah Sari; Andy Dharmalau; Riza Syahrial (Institut Teknologi dan Bisnis (ITB) Swadharma, 2022)
The students to graduate and get a degree are required to make a Job Training and Final Reportt. So that accumulated many reports that must be recorded every year. All these reports should be recorded and saved to the storage media. The recording process currently carried out uses a recording system in a book. This recording system becomes a problem when making periodic reports for the data collection on Job Training Reports and Final Projects. Besides the problems in reporting, there are also difficulties when wanting to find out which students have submitted reports or not, because there is no system that can display the latest data. The results of research to make to solve the problems that occur require an information system. For this reason, a system of application for the data collection on Job Training Reports and Final Projects is designed. The results of the system design have met technological, operational, and legal feasibility so that they are suitable for use